Value-Based Management in Government: A Systematic Review and Transferable Architecture for Indonesia - Rizky Ridho Dwinanda; Anak Agung Gde Satia Utama (Universitas Sultan Ageng Tirtayasa, 2026)
Indonesia’s bureaucratic reform increasingly demands a shift from procedural compliance to citizen-experienced outcomes. Q1 2025 records 2,955 complaints to the Ombudsman—dominated by personnel administration and agrarian/land affairs—signalling persistent frictions that current controls fail to resolve. This study maps opportunities and constraints for adapting Value-Based Management (VBM) to Indonesia’s public sector. It offers a transferable, auditable architecture that links outcomes, managerial mechanisms, institutional conditions, and evaluation designs. Methods follow PRISMA-2020 for a systematic review of peer-reviewed studies on VBM in government; five eligible studies spanning healthcare, local government, higher education, and infrastructure were synthesized. To address the small academic corpus and improve field realism, the synthesis is calibrated with Indonesian administrative indicators (Ombudsman 2024–Q1 2025); these do not enter formal synthesis but inform external validity and implementation choices. Results identify opportunity domains—outcome-based funding, patient-reported outcome measures, and portfolio discipline—alongside cross-cutting challenges: legacy control logics, gaming risks, uneven subnational capacity, and data-governance/privacy constraints. The proposed architecture organizes “outcome families” (timeliness, accessibility, fairness, error-correction, and fiscal prudence). It specifies implementable routines (distribution-based targets, performance dialogues, transparent dashboards, and an anti-gaming playbook) with an evaluation path using quasi-experimental designs. We conclude that VBM is feasible for Indonesia if coupled with risk adjustment, distributional metrics, and safeguards for equity and privacy. Limitations include a small evidence base; future work should test pilots in high-volume services and pre-register impact evaluations.